‘The Towers of Terror’: A Critical Analysis of Ernő Goldfinger’s Balfron and Trellick Towers - Braghieri, Nicola (2019)
When J. G. Ballard published his masterpiece High-Rise in 1975, many readers in London automatically identified the apartment building that is the protagonist of the dystopian novel as the infamous Trellick Tower at Kensal Town, certainly one of the most controversial and ambiguous figures of British architecture after World War II. Designed by Ernő Goldfinger, the tower, which had recently been completed, was already considered a symbol of the brutality of contemporary architecture, to the point of gaining the nickname ‘Tower of Terror’ coined by its own inhabitants. Actually, in public opinion the nearly twin sister of the earlier Balfron Tower at Poplar embodied all the ills of urban planning and of the housing policies of the post-war reconstruction. The large size of the project, the uniformity of its facades, the presence of bulky stairwells separated from the main volume, connected by elevated bridges and brandishing the big chimneys of the heating system, the complex apartment layouts on multiple levels, and the intensive use of fair-face reinforced concrete are the factors that shape the extraordinary character of this work of architecture, examined in a relatively small quantity of critical writings, despite the building’s widespread notoriety. The Balfron Tower, commissioned in 1963, and the Trellick Tower commissioned in 1966 have become, for better or worse, icons of British public housing policy, and today they are inseparable parts of the London cityscape. Critical analysis of the original project documents reveals how the typological and constructive reflections at the end of the 1960s had reached a level of extreme sophistication and quality, also in the development of large social housing complexes created for the urban proletariat. Thanks to their outstanding constructed quality and the efficacy of their residential typologies, the towers have stood up to the destructive fury of the last few decades, even becoming Grade II* listed buildings. In recent years, they have gone through a remarkable process of social and generational turnover, coveted as investment properties and involved in processes of real estate speculation.